2016
DOI: 10.1038/srep18822
|View full text |Cite
|
Sign up to set email alerts
|

AGE-RAGE signal generates a specific NF-κB RelA “barcode” that directs collagen I expression

Abstract: Advanced glycation end products (AGEs) are sugar-modified biomolecules that accumulate in the body with advancing age, and are implicated in the development of multiple age-associated structural and functional abnormities and diseases. It has been well documented that AGEs signal via their receptor RAGE to activate several cellular programs including NF-κB, leading to inflammation. A large number of stimuli can activate NF-κB; yet different stimuli, or the same stimulus for NF-κB in different cellular settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…Most importantly, collagen I diminished to a level below the one registered in BSA and nonimmune murine IgG exposed cells, suggesting RAGE may be involved (via NF-κB signaling) in steady state collagen I expression in these cells. Recently, collagen type I expression was shown to be induced in a very specific manner by NF-κB p65 via the AGEs-RAGE axis [ 59 ]. This is in accordance with our findings which showed that anti-RAGE antibody treatment severely diminished NF-κB p65 ( Fig 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, collagen I diminished to a level below the one registered in BSA and nonimmune murine IgG exposed cells, suggesting RAGE may be involved (via NF-κB signaling) in steady state collagen I expression in these cells. Recently, collagen type I expression was shown to be induced in a very specific manner by NF-κB p65 via the AGEs-RAGE axis [ 59 ]. This is in accordance with our findings which showed that anti-RAGE antibody treatment severely diminished NF-κB p65 ( Fig 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both of these pathways activate NF κ B, which would allow for the conclusion that RAGE signaling increases NF κ B activity [ 69 ]. An increase in NF κ B transcription activity can lead to an increase in mRNA expression of type I collagen a1 and a2 in murine VSMCs treated with AGEs as shown in Peng et al [ 70 ]. Collectively, AGE-induced RAGE signaling affects the activity of NF κ B in VSMCs, which can lead to remodeling of the type I collage in the ECM or to a change in cell morphology.…”
Section: Age-rage Signaling and Oxidative Stress In Vascular Calcimentioning
confidence: 99%
“…However, we found increased activation of the NF-κB pathway as demonstrated by the increased p-IκB/t-IκB ratio in association with decreased c-Met phosphorylation, as well as increased levels of TNFα and IL-6 in crizotinib-treated mice compared to control counterparts. TNF family cytokines can activate the NF-κB signaling pathway and NF-κB activation can induce collagen expression and cause tissue fibrosis in a TGFβ-independent fashion [ 35 , 36 , 37 ]. The NF-κB pathway may also cause tissue fibrosis by promoting differentiation of epithelial cells to fibroblasts [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%